THE APPLICATION OF CULTURAL TEXTS AS AN AUTHENTIC MATERIAL IN INDONESIAN LANGUAGE FOR FOREIGN LEARNERS - Dakia N. Djou, Liem Gai Sin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to describe the impact of the application of cultural texts as an authentic material in Indonesian Language for Foreign Learners (BIPA). It indicates that after learning story texts, the foreign learners have some improvements in speaking. In addition, generates their strong motivation to learn Indonesian since the messages and objectives in the text could be easily comprehended. The upshot of this paper is that Indonesian cultural texts could highly assist students to overcome their learning gaps and are beneficial to be used for learning materials.